Theoretical-Methodological Problems of Service Sector Development - Urunbayeva Yulduz Pirnazarovna; Fayzullayeva Sabrina Uyg‘un qizi (Research Parks Publishers, 2023)
The article emphasizes that the development of the services sector is a key factor in the socio-economic development of the country.